PENERAPAN BERBAGI KEUNTUNGAN DAN KERUGIAN DALAM PEMBIA AAN MURABAHAH DI BANK S ARIAH INDONESIA - Ahmad Supriyadi (UNISSULA, 2017)
The research on profit and loss in the transactions of Islamic banks aims to explore the applicationof the law and find the factors of application of the law of sharing profit and loss in murabahahfinancing in Bank Syariah Indonesia that has not provided justice. Is a qualitative empirical lawresearch with problem solving approach through case approach, normative, juridical and thetype of research is field research or field research, then do also observation and analysis withinductive method so that problem formulated can be resolved. The result of this research isthe application of law about share of profit and loss in murabahah financing in Bank SyariahIndonesia has not give justice factor is three things that is weakness from side of law substance,legal structure and law culture.